Nasogastric aspiration/lavage in patients with gastrointestinal bleeding: a review of the evidence. (2nd January 2018) - Karakonstantis, Stamatis; Tzagkarakis, Emmanouil; Kalemaki, Dimitra; Lydakis, Charalampos; Paspatis, Gregorios
ABSTRACT: Introduction : The usefulness of nasogastric aspiration and nasogastric lavage in patients with gastrointestinal bleeding is controversial, as evidenced by conflicting recommendations, both among and within society guidelines. Areas covered : Considering these controversies, we reviewed the evidence regarding the following questions: 1) Can nasogastric lavage stop or slow down the bleeding and improve subsequent endoscopic visualization? 2) Is nasogastric aspiration helpful for the localization of bleeding? 3) Can nasogastric aspiration identify high risk patients that might benefit from earlier endoscopy? 4) Is there evidence for benefit in terms of outcomes from using nasogastric aspiration? 5) Is nasogastric intubation safe in patients with possible esophageal varices? Our review was conducted according to PRISMA guidelines. Expert commentary : Based on the available literature, nasogastric lavage or aspiration cannot be routinely recommended unless a large properly designed randomized trial (which is currently lacking) proves otherwise. It is a painful and time-consuming procedure with no demonstrated benefit for the patient in terms of outcomes. Other clinical and laboratory parameters, and risk scores, are less invasive and are effective for guiding the stratification and management of patients, while pre-endoscopic erythromycin infusion is a good if not better alternative for improving visualization of the stomach.